The Influence of Service Quality on Student Loyalty at Budi Bakti Tutoring - Julianti, Geshapillia; Februadi, Agustinus C.; Safaruddin (Journal of Marketing Innovation (JMI), 2023)
Education is considered one of the important primary human needs. Therefore, people are competing to get the best educational place. This phenomenon encourages parents to register their children with tutoring institutions to get additional classes. Tutoring in Indonesia is included in the Course and Training Institute (LKP). During the pandemic, LKP's growth declined due to the loss of students. The decrease in student enrollment also occurred in one of the tutoring institutions in Bandung Regency, namely the Budi Bakti Tutoring Institute. In services, service quality is an essential factor in the competitiveness and sustainability of institutions. The purpose of this study is to assess the level of service quality at Budi Bakti Tutoring to retain existing students and gain new students by measuring the five dimensions of service quality perceived value, student satisfaction, and student loyalty. The research method used is a quantitative approach. In this approach, data collection was carried out on 222 samples of students and alumni of Budi Bakti Tutoring through the distribution of questionnaires and then analyzed with PLS-SEM. The results showed that there was a positive influence between service quality on perceived value, student satisfaction, and student loyalty. This research is expected to improve the quality of service at Budi Bakti Tutoring.